The Limits of Nuclear Non-Proliferation: Legal Oversight, Safeguards, and Compliance under the 1968 NPT - Ramlan, Ramlan; Suhermi, Suhermi; Sasmiar, Sasmiar; Mardhatillah, Mardhatillah (Uti Possidetis: Journal of International Law, 2025)
Background: The 1968 Non-Proliferation Treaty (NPT) is the cornerstone of the global nuclear non-proliferation regime, aiming to regulate the peaceful use of nuclear energy, prevent the spread of nuclear weapons, and promote gradual nuclear disarmament. Its principles seek to reduce nuclear threats and create a safer international security environment while preventing future remilitarization. Purpose: This study aims to assess the effectiveness of the NPT in enforcing compliance and preventing proliferation, as well as to identify the main challenges that hinder its successful implementation. Methodology: The research employs a normative legal approach by reviewing NPT provisions, IAEA official reports and instruments, and case studies involving states suspected of developing clandestine nuclear programs. Findings: The International Atomic Energy Agency (IAEA) serves as the primary verification body for NPT compliance through its safeguards system. However, enforcement remains challenging, particularly when states conceal nuclear activities. Limited inspection access exemplified by Iran’s decision not to ratify the Additional Protocol, makes it difficult for inspectors to verify undeclared nuclear materials and activities. Furthermore, several structural weaknesses reduce the NPT’s overall effectiveness, including reliance on the political will of the international community, imbalances between nuclear-weapon states (NWS) and non-nuclear-weapon states (NNWS), insufficient penalties for violations, and the Escape Clause that allows withdrawal from the treaty. Originality/Value: This research provides a critical evaluation of the NPT safeguard and verification mechanisms, highlighting practical implementation obstacles and their implications for the future of the global non-proliferation regime.